2021
DOI: 10.3390/antibiotics10080930
|View full text |Cite
|
Sign up to set email alerts
|

Treating Critically Ill Patients Experiencing SARS-CoV-2 Severe Infection with Ig-M and Ig-A Enriched Ig-G Infusion

Abstract: SARS-CoV-2 in patients who need intensive care unit (ICU) is associated with a mortality rate ranging from 10 to 40–45%, with an increase in morbidity and mortality in presence of sepsis. We hypothesized that IgM and IgA enriched immunoglobulin G may support the sepsis-related phase improving patient outcome. We conducted a retrospective case–control study on 47 consecutive patients admitted to our ICU. At the time of admission, patients received anticoagulants (heparin sodium) together with the standard suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(52 reference statements)
2
3
0
Order By: Relevance
“…Our data show a significant difference in sodium concentration in non-severe vs. severe patients (136 mmol/L vs. 127 mmol/L, p = 0.007), which is in agreement with a study carried out by Guan et al where non-severe COVID-19 patients also showed high sodium [31,32]. In our study, patients who died (131 mmol/L) had higher sodium concentrations compared to surviving patients (128 mmol/L) (p = 0.403), showing that a high concentration of sodium could be a protective biological factor against an unfavorable clinical outcome.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data show a significant difference in sodium concentration in non-severe vs. severe patients (136 mmol/L vs. 127 mmol/L, p = 0.007), which is in agreement with a study carried out by Guan et al where non-severe COVID-19 patients also showed high sodium [31,32]. In our study, patients who died (131 mmol/L) had higher sodium concentrations compared to surviving patients (128 mmol/L) (p = 0.403), showing that a high concentration of sodium could be a protective biological factor against an unfavorable clinical outcome.…”
Section: Discussionsupporting
confidence: 93%
“…The higher frequency of patients without antibodies IgG is not surprising, as patients were recruited early after disease onset, presumably without having yet developed a humoral response to infection. The increase in IgG antibodies with the severity of the disease is expected and is in accordance with the profile of the immune response to SARS-CoV-2 infection [30,31]. In agreement with our results, Marklund et al showed that patients with severe COVID-19 seroconvert earlier and develop higher concentrations of SARS-CoV-2specific IgG compared to patients with non-severe disease, which could improve patient outcomes [30].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, there were some case reports and small studies regarding the usage of Pentaglobin as adjunctive therapy in COVID-19 (185)(186)(187)(188). Although in a large retrospective cohort study, no significant difference in mortality was observed (n=316, p=0.374), a subgroup of severe COVID-19 patients who have not yet received invasive mechanical ventilation may benefit from Pentaglobin therapy (p=0.063).…”
Section: Pentaglobinmentioning
confidence: 99%
“…One retrospective case-control study in COVID-19 reported that treatment with an IgM/IgA-enriched Ig preparation significantly (p = 0.045) reduced the number of patients developing septic shock compared with the control group (12.5% (3/24) vs. 21.7% (7/23)) and, accordingly, the mortality rate (Table 2, [175]).…”
Section: Clinical Studies Investigating the Supporting Role Of Polyva...mentioning
confidence: 99%